The Impact Of Garnier Green Product, Green Promotion, And Green Perceived Value On Millennial Purchasing Intention In Medan - Grace Margareth Ginting; Feby Aulia Safrin (Journal Boas : Business, Economics, Accounting And Management, 2022)
Company officials realize that sustainability issues will be very beneficial in facing today's business competition. Garnier is one of the top three brands chosen by Indonesian consumers, which implements sustainability through the Garnier Green Beauty program. This research aims to analyze how Garnier green products, green promotion, and green perceived value partially and simultaneously affect millennial purchasing intentions in Medan by using a quantitative form with an associative approach. The samples were taken with a purposive sampling technique and used 100 respondents. The data were obtained by primary data and secondary data. The methods of data analysis that were used are validity tests, reliability tests, classic assumptions tests, multiple linear regression analysis, and hypothesis tests. The results showed that Garnier green product, green promotion, and green perceived value partially and simultaneously influence millennial purchasing intention of products in Medan. The coefficient test of determination with an R-value is 0.809. The Adjusted R Square value showed that the green product, green promotion, and green perceived value can explain the purchase intention by 64.3%, while the remaining 35.7% is influenced by other variables not discussed in this research.